2009
DOI: 10.1007/s10295-009-0629-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification of functionally clustered nystatin-like biosynthetic genes in a rare actinomycetes, Pseudonocardia autotrophica

Abstract: The polyene antibiotics, including nystatin, pimaricin, amphotericin, and candicidin, comprise a family of very valuable antifungal polyketide compounds, and they are typically produced by soil actinomycetes. Previously, using a polyene cytochrome P450 hydroxylasespeciWc genome screening strategy, Pseudonocardia autotrophica KCTC9441 was determined to contain genes potentially encoding polyene biosynthesis. Here, sequence information of an approximately 125.7-kb contiguous DNA region in Wve overlapping cosmids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 38 publications
1
44
0
Order By: Relevance
“…The bioinformatically identified selvamicin cluster resembles known type I PKS-derived polyene BGCs (30)(31)(32)(33)(34)(35), and a side-by-side comparison with the well-characterized nystatin BGC (36,37) readily reveals the origins of selvamicin's unusual structural features (Fig. 5).…”
Section: Chemistrymentioning
confidence: 91%
“…The bioinformatically identified selvamicin cluster resembles known type I PKS-derived polyene BGCs (30)(31)(32)(33)(34)(35), and a side-by-side comparison with the well-characterized nystatin BGC (36,37) readily reveals the origins of selvamicin's unusual structural features (Fig. 5).…”
Section: Chemistrymentioning
confidence: 91%
“…PikD, the only regulator in the pikromycin cluster, positively regulates the production of pikromycin in Streptomyces venezuelae (Wilson et al, 2001). In some cases, multiple LAL-type regulators are present in the same cluster, especially in polyene antibiotic biosynthetic clusters, such as NysRI-NysRIII of the nystatin cluster in S. noursei ATCC 11455 (Sekurova et al, 2004), AmphRI-AmphRIII of the amphotericin pathway in S. nodosus (Carmody et al, 2004), NppRI-NppRIII of the NPP cluster in Pseudonocardia autotrophica (Kim et al, 2009) and CanORF1-CanORF3 of the candicidin pathway in Streptomyces griseus (Campelo & Gil, 2002). Most of the time, these LAL-type regulators are clustered with a PimM-like regulator, as seen in the biosynthetic gene clusters for nystatin, amphotericin and NPP (Carmody et al, 2004;Kim et al, 2009;Sekurova et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Candicidin is frequently re-isolated and its biosynthetic gene cluster appears in several genomes (Jorgensen et al, 2009;Seipke et al, 2011b;Olano et al, 2014;Tang et al, 2015;Komaki et al, 2015;Liu et al, 2015a). Since the sequencing of the nystatin biosynthetic genes in S. noursei (Brautaset et al, 2000), at least three other closely related clusters have been found (Kim et al, 2009;Barke et al, 2012;Cui et al, 2015). Pimaricin is produced by S. natalensis, Streptomyces gilvosporus, Streptomyces lydicus and Streptomyces chattanoogensis (Aparicio et al, 2016).…”
Section: Genes For Polyene Macrolide Biosynthesismentioning
confidence: 99%